Imaginary Aesthetic Territories: Australian Japonism in Printed Textile Design and Art - Giambazi, Kelsey Ashe (Curtin University, 2018)
This creative production thesis considers how Japanese aesthetic philosophies have influenced textile design and art by examining its use, significance and representation in fashion and art in Australia. Correlations between the space indicated in Japanese pictorial principles and the open space of the Australian landscape are considered, as are the conventions of constructed exoticism inherent to Japonism. The thesis and creative works respond to issues of Australian cultural identity, hybridity, orientalism and cultural yearning.